Mechanical And Biodegradable Properties Of Hydroxyapatite Coated Magnesium Deposited By Cold Spray - Razi, Hasniyati Md (2016)
A simple and modified cold spray process was developed in which hydroxyapatite powder was coated onto pure magnesium substrates preheated to 350°C or 550°C and ground to either 240 grit or 2000 grit surface roughness, with standoff distances of 20 mm or 40 mm. The procedure was repeated five and ten times. A fractional factorial design (24-1) was applied to elucidate the process factors that significantly affected the thickness, nanohardness and elastic modulus of the coating sample. The overlaid method analysis was employed to determine trade off optimal values from multiple responses. Then, steepest method was used to reconfirm and relocate the optimal domain. The maximum mechanical properties of the coating were determined at 30mm standoff distance, surface roughness Ra=0.14μ and 460°C substrate heating temperature which accommodate the optimum coating of 49.77μm thickness, 462.61 MPa nanohardness and 45.69 GPa elastic modulus. The hydroxyapatite coatings did not show any phase changes at 550°C. Atomic force microscopy revealed a uniform coating topography and scanning electron microscopy revealed good bonding between the coated layers and the substrates. The biodegradable study suggested that bone-like apatite layer formed on the surface of the coatings at 2 hours may promote bone bonding with living tissues and increase the longevity of coatings. The mass loss experiment concluded that coated sample shows a better bioactivity compared to uncoated sample. The adhesion test revealed that reduction of bond strength comes mostly from the continuation of chemical dissolution of coatings. After 24 hours of immersion, the bond strength was 40 MPa which satisfied the requirement for bioimplant application. The accelerated corrosion test concluded that the hydroxyapatite coating remarkably protect and prevent magnesium from corrosion in the corrosive environment.